STATUS OF DISABILITY IN INDIA - 2007 Vol.1 - Hearing Impairment & Deaf Blindness - N, Rathna (Journal of All India Institute of Speech and Hearing, 2009)
Book Review on ‘Status of Disability in India – 2000, 2003 and 2007’. The latest book ‘STATUS OF DISABILITY IN INDIA –2007’ was published in the year 2008.